The use of screw driving sounding in soil assessment in Metro Manila, Philippines - Daag, Arturo; Sochayseng, Katelyn; Arnoco, Earl Joyce; Serrano, Andrew; Solidum, Renato (Geotechnical research, 2023)
A coastal portion of the Greater Metro Manila Area, Philippines, is situated primarily on Quaternary alluvium deposits, which are likely to liquefy. Liquefaction is a hazard that occurs when loosely packed, saturated sediments at or near the ground surface lose their strength, caused by an earthquake. Currently, the standard in determining the soil properties and liquefaction potential of a site is by using conventional geotechnical techniques such as the standard penetration test (SPT). However, this method has disadvantages in terms of cost, logistics and workforce. The screw driving sounding (SDS) test was developed to estimate equivalent SPT parameters such as N-value and fines content, which are then used for liquefaction analysis. This paper presents a comparative analysis between SDS and SPT in selected schools in the Greater Metro Manila Area, Philippines. Moreover, soil classification and site-specific liquefaction potential evaluation were also estimated using the data acquired from the SDS test. Overall, the results of the study prove that the SDS test is an effective alternative method for soil investigation and estimation of the liquefaction potential.